1976
DOI: 10.1021/jo00878a034
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of nitrogen compounds with ruthenium tetroxide. 2. Oxidation of tertiary amines as a convenient alternative to von Braun degradation

Abstract: Notes 2-Chloromethyl-5-hydroxy-4-pyrone (3), mp 165-166 °C (lit.30 mp 166-167 °C).2-Hydroxymethyl-5-methoxy-4-pyrone (5), mp 119-120 °C (lit.31 mp 119-121 °C).2-Acetoxymethyl-5-aCetoxy-4-pyrone (6). This material was prepared by acetylation of kojic acid, mp 100-102 °C (lit.32 mp 102 °C).Comenic Acid (7). This.compound was prepared by catalytic oxidation pf kojic acid, mp 220 °C dec (lit.33 mp not specified).Hydroxymaltol (2-hydroxymethyl-3-hydroxy-4-pyrone) (9), mp 149-151 °C (lit.34 mp 152-153 °C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

1978
1978
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 2 publications
0
13
0
1
Order By: Relevance
“…Oxidation was performed in the same conditions as above [2,3,7,8], that is with catalytic amounts of RuO 4 (generated in situ from catalytic RuO 2 and excess NaIO 4 ), in CCl 4 /water heterogeneous mixtures and at room temperature. The reaction mixtures were worked-up in two ways (A or B ; see Section 3.8), differing by the order of operations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Oxidation was performed in the same conditions as above [2,3,7,8], that is with catalytic amounts of RuO 4 (generated in situ from catalytic RuO 2 and excess NaIO 4 ), in CCl 4 /water heterogeneous mixtures and at room temperature. The reaction mixtures were worked-up in two ways (A or B ; see Section 3.8), differing by the order of operations.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, earlier studies indicated 4-benzoylmorpholine and 4-benzyl-3-morpholinone as reaction products obtained from 4-benzylmorpholine [2], meaning that both types of N -α-sites (i.e., exocyclic and endocyclic, respectively) were attacked. In the same reaction conditions, 1-benzylpiperidine yielded only products of endocyclic attack [3]. Same exclusive endocyclic functionalization showed also some piperazine derivatives (Scheme 1).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In a previous paper 1 we studied the RuO 4 -mediated oxidation 2 of some N-benzylated cycloalkylamines and found that the attack occurs at both types of N-α-methylene positions, 3 i.e., endocyclic and exocyclic (benzylic). Proof of the incursion of the corresponding iminium cations as intermediates came from their capture as nitriles in the presence of cyanide anion (cyano trapping).…”
Section: Introductionmentioning
confidence: 99%